Consideration of Official Village Head Given Obligation as Mediator in Solving Land Rights Dispute among Villagers in Indonesia - Munawir, La Ode; Safa’at, Rachmad; Negara, Tunggul Anshari Setia; Koeswahyono, Imam (International Journal of Social Sciences and Management, 2018)
Village head act as mediator in solving villager’s dispute. However, on the other hand, village head act as implementer of village governance. Therefore, questions arise concerning why village head should become the mediator in solving villagers’ dispute, concerning mediator should be neutral side in reconciliate all related parties. Method used in this study was normative legal research with philosophical approach, concepts, cases, history and statute approach. Theories and concepts used in this dissertation includes legal objectives theory, authorization theory, dispute solving theory. Results and discussion: Consideration of village head given obligation as mediator in solving villager’s land rights dispute, village head act as implementer of village governance, with the authority given by statute and authority based on origins, village head acts as the village reconciliation judge. The existence of village governance was very close with the villagers itself starting from the head’s involvement in land registration process until it was presume that village head was knowledgeable concerning land history within the village border. However, on the other hand, village head has many authorities that should be implemented. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 83-88